The genus Acellomyia González, a new taxonomic arrangement of its species and descriptions of a new genus and two new species from southern South America (Diptera: Tabanidae: Diachlorini) - González, Christian R. (Zootaxa, 2017)
The tabanid tribe Diachlorini (Diptera) is the most genus-rich tribe in the Tabanidae; the tribe is cosmopolitan, but the greatest species richness and morphological diversity are found in the Australasian and Neotropical Regions. A new arrangement for the species of Acellomyia González is given; Acellomyia lauta (Hine) is transferred to a new genus, Montismyia gen.n., based on its morphological differences from Acellomyia and geographical distribution. The morphological differences between Acellomyia and Montismyia gen. n. are discussed. Two new species, Acellomyia casablanca sp.n. and Acellomyia puyehue sp.n., are described from specimens collected in southern Chile. Comparison of the morphology of Acellomyia paulseni mapuche (Coscarón & Philip) stat.nov. indicate that they should be elevated to species rank. A key to species of Acellomyia is provided and diagnostic characters are illustrated.